Menstrual Cycle Disorders in Adolescents - Rizki Khaerunnisa Sappe, Alda; Triana Oktavia, Amanda; Chairunnisa, Asadini; Mareta Undaryat, Yeti (Riviera Publishing, 2024)
Adolescence is an important transition period for women's reproductive health, characterized by a variety of physiological changes including the menstrual cycle. Menstrual cycle disorders, such as dysmenorrhea, oligomenorrhea, and amenorrhea, are common and can affect the quality of life of adolescent girls. This study aims to analyze the prevalence, risk factors, and impact of menstrual cycle disorders in adolescents in Indonesia through a literature reflection of articles published between 2019 and 2024. The results showed that about 67.8% of adolescent girls experienced at least one type of menstrual disorder, with dysmenorrhea being the most common complaint. Factors that affect this disorder include physical activity, stress levels, nutritional status, and body mass index. This research is expected to provide a scientific basis for the development of more effective prevention and treatment strategies for menstrual cycle disorders in adolescents.